Dramatization on Television News: Approach of Experts and Challenges in the Context of Disinformation - Ščavinskaitė, Kamilė (Jaunųjų mokslininkų darbai, 2025)
In the age of immeasurable amounts of information, with the rapid spread of modern information solutions and ongoing search for new forms of information transfer, the design of content is changed and entangled in various kinds of emotions. One of the most commonly used techniques is dramatization, which aims to provoke a strong emotional response from the viewer. However, in the contemporary media landscape characterized by disinformation and manipulation, this phenomenon is emerging as a cause for concern.
Keywords: dramatization; television; news selection; disinformation